2014
DOI: 10.1371/journal.pcbi.1003907
|View full text |Cite
|
Sign up to set email alerts
|

Robust Identification of Noncoding RNA from Transcriptomes Requires Phylogenetically-Informed Sampling

Abstract: Noncoding RNAs are integral to a wide range of biological processes, including translation, gene regulation, host-pathogen interactions and environmental sensing. While genomics is now a mature field, our capacity to identify noncoding RNA elements in bacterial and archaeal genomes is hampered by the difficulty of de novo identification. The emergence of new technologies for characterizing transcriptome outputs, notably RNA-seq, are improving noncoding RNA identification and expression quantification. However,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 67 publications
2
60
0
Order By: Relevance
“…Despite the prevalence of sRNAs in many bacteria, there exists only limited evolutionary conservation and both species- and strain-specific sRNA catalogues are now documented22. A search of 400 transcriptomic datasets belonging to 40 different strains of bacteria and archaea has revealed that the ‘Goldilocks Zone’ (where species are neither too close nor too distant phylogenetically) for non-coding RNAs is rather narrow, indicating independent evolution of lineage-specific post-transcriptional machinery23. As further confirmatory evidence supporting this notion, a search for orthologs of 2208 non-coding RNAs within 1156 bacterial genomes reported in Rfam (a collection of non-coding RNA families)24, including members of Rickettsiales , also reveals limited taxonomic distribution and suggests a low degree of evolutionary conservation in a majority of these ncRNA families25.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the prevalence of sRNAs in many bacteria, there exists only limited evolutionary conservation and both species- and strain-specific sRNA catalogues are now documented22. A search of 400 transcriptomic datasets belonging to 40 different strains of bacteria and archaea has revealed that the ‘Goldilocks Zone’ (where species are neither too close nor too distant phylogenetically) for non-coding RNAs is rather narrow, indicating independent evolution of lineage-specific post-transcriptional machinery23. As further confirmatory evidence supporting this notion, a search for orthologs of 2208 non-coding RNAs within 1156 bacterial genomes reported in Rfam (a collection of non-coding RNA families)24, including members of Rickettsiales , also reveals limited taxonomic distribution and suggests a low degree of evolutionary conservation in a majority of these ncRNA families25.…”
Section: Discussionmentioning
confidence: 99%
“…High degrees of both intra- and inter-species polymorphism yield low sequence similarity, especially as compared to protein-coding genes, and sRNAs on the whole are known to be poorly conserved across broad evolutionary distances (6). Comparing the contents of Rfam (7)—a database that houses sequence and structural information for known sRNA families—to Pfam (8), an analogous database for protein families, only 60% of RNA families were found to be conserved between species of the same taxonomic family, as opposed to 90% for proteins (9). In evolutionary analyses, where a clear picture of relationships between gene sequences through time is critical in order to draw meaningful conclusions, this presents the unique challenge of distinguishing between an sRNA’s absence in a given lineage and the possibility that the sequence or structure of the gene has simply diverged too drastically to accurately trace its ancestry.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of functional non-coding RNAs (ncRNAs), like transfer RNA and catalytic RNAs, led to the proposal of an ancestral RNA world, where RNA both catalyzes the reactions of life and encodes genetic information (3) . Despite the importance of non-coding RNAs to cellular function, many RNAs exhibit low sequence conservation and are not as broadly distributed as their proteinaceous brethren (4) . In contrast, proteins make up the bulk of the biomolecular contents of the cell, and are required for the majority of critical cellular structures and functions.…”
Section: Introductionmentioning
confidence: 99%